KELAYAKAN MEDIA FLIPBOOK DARI CERITA RAKYAT "NE"™ BARUAKNG KULUB" PADA SUBMATERI KELOMPOK HEWAN - Pamane, Yusta Vera; Candramila, Wolly; Tenriawaru, Andi Besse (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2024)
The moral values and local wisdom contained in folklore can be used as a communication tool to teach educational values, and can also be used as a learning resource in schools. This research aims to determine the feasibility of a flipbook that highlights the diversity of animals in the Ne' Baruakng Kulub folklore in the Animal Group sub-material. The method used is research and development (RD) according to Borg Gall. The steps used include 3 of 10 stages, namely research and gathering information through studying literature related to animals found in folklore, followed by planning to formulate learning objectives which will be mediated by flipbook media in accordance with basic competencies, and developing initial forms of product by making a flipbook according to the results of research and gathering information and planning. The flipbook media product was assessed by 5 validators consisting of 2 Biology Education lecturers and 3 Science teachers. Data analysis uses Content Validity Ratio (CVR) and Content Validity Index (CVI) referring to the Lawshe method. The folk tale "Ne' Baruakng Kulub" is presented in flipbook media in the form of a synopsis and the types of animals contained in the story are used as a means to link it to the learning material. The flipbook media was assessed as appropriate by the five validators on all criteria with CVR and CVI values equal to 1. Thus, the Animal Group Submaterial flipbook media based on the folklore "Ne'Baruakng Kulub" was suitable for use as a learning medium.